Mudanças climáticas e os objetivos do desenvolvimento sustentável: cenário atual e possíveis caminhos para a formação de um município resiliente - Ottaviano, Schennia (2019)
Mapping environmental risks in the organization of municipalities encompasses the notion of vulnerability. Situational analysis based on territorial indicators can guide climate change at a lower level, helping to understand this issue from a systemic perspective. Understanding the theme translates into development, sustainability, community organization and the deployment of leadership for this transition phase. It is an action plan for integrating social inclusion, environment and economy. For a complex area, we also need complex thoughts and this goes through interdisciplinarity, highlighting here the need to encourage further research in this area, in all fields of knowledge. In the study of this dissertation, two articles are presented. The first article deals with climate change and sustainable rural development in the municipality of Marechal Cândido Rondon, which depends on agriculture in its economy. From the collection of climate data from a local experimental station, the research objective highlights changes in the climate pattern of the region. Data were collected demonstrating indications of minimum temperature increase over a ten year interval. There is also an increase in days with temperatures above 20 ° C within the measurements. It is hypothesized that these high temperatures influenced a corn leafhopper infestation in this year's crops, throughout the municipality and especially in the district of Porto Mendes, causing crop losses. In addition, socio-economic structures, infrastructure services that help the municipality become less vulnerable and more resilient to climate change are mapped. A second article outlines the contributions that Psychology can make in emergencies and disasters. The objective is to highlight the help of rescue teams, as well as the reorganization of the population to cope with traumatic situations. The article also addresses the issue of environmental disaster risk management from the notions of complexity and the involvement of the population as a whole.